PERAN PENCATATAN KEUANGAN DALAM PENGAMBILAN KEPUTUSAN USAHA PADA WIRAUSAHA PEMULA - Syamsinar, Syamsinar; Nuryati, Siti; Khalishah, Khansa; Jafar, Adindah Novihartina; Ma'shum, Muhammad (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to determine the role of financial record keeping in business decision-making for start-up entrepreneurs. This research approach collected data through a literature review, involving reading literature from various sources, including books, articles, journals, and reports, using qualitative and deductive approaches. The results of this study indicate that financial record keeping plays a strategic role in supporting business decision-making, particularly for start-up entrepreneurs. By recording cash flow, profit and loss statements, and accounts payable and receivable data, entrepreneurs can monitor financial health, prepare budgets, and objectively evaluate business performance. Financial data also serves as the basis for determining capital requirements, accessing funding sources, and preventing financial irregularities through improved internal controls. Furthermore, financial record keeping plays a crucial role in fulfilling legal obligations, particularly regarding tax reporting, thereby enhancing business credibility and sustainability. With good financial record keeping, start-up entrepreneurs can make more informed business decisions, reduce financial risks, and enhance long-term business sustainability